Uwagi o instytucji przedawnienia w projekcie polskiego kodeksu karnego z 1932 roku - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article is devoted to the statute of limitations in the draft Polish criminal code of 1932. The author discusses the origins of the code, the work of the Criminal Law Section of the Codification Commission of the Republic of Poland, and the legal structure of the regulations.He demonstrates that the statute of limitations in the draft Polish criminal code of 1932 was shaped by in-depth reflection taking into account the European doctrine of law. When it comes to the statute of limitations, the Polish criminal code sought to systematise it practically, also on thebasis of experiences with the existing legislation. As a result, the draft code introduced three types of limitation: applying to prosecution, verdicts and sentencing.
Keywords: Komisja Kodyfikacyjna II Rzeczypospolitej Polskiej; projekt kodeksu karnego; przedawnienie; Makarewicz, Juliusz (1872-1955)